Pengembangan Metode Autentikasi pada Sistem Presensi Berbasis Aplikasi Mobile - Komang Sri Utami; Nyoman Putra Sastra; Dewa Made Wiharta (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Research has been carried out on a mobile-based presence system authentication method using MAC addresses, BSSID and IP addresses for (Wi-Fi) networks. This study aims to develop an authentication method on the attendance system that meets two authentication requirements, namely the suitability of employee identity and location suitability, so that the attendance process becomes easy, effective, fast, and can reduce fraud. The employee's identity can be obtained from the MAC address of the smartphone that has been previously registered, while the employee's location during the attendance process can be confirmed to be in the company environment by checking the BSSID data and IP of the Wi-Fi network connected to the smartphone. The data is then compared with MAC address data from all Wi-Fi networks installed in the company area. RAD is used as a development model because it is simple and fast. Overall, employee identification and site checking as authentication of the developed system went well. Other than that, every function on the system works well. Furthermore, the results of the user experience evaluation using the UEQ questionnaire received an average score above 0.8 on 6 scales. This shows that the system has attractiveness, perspicuity, efficiency, dependability, stimulation and novelty.